Respiratory tract infections - Always a trigger for developing dka in children with type 1 diabetes? - Andreia Mihaela Condrea; Alina Corina Grama; Ovidiu Grama (Amaltea Medical Publishing House, 2023)
Respiratory tract infections are usually the most common infections in pediatric patients, including in those with diabetes. A low control on the glucose levels makes the diabetic patient more vulnerable to get an infectious disease and even to develop serious complications, such as diabetic ketoacidosis. We present you two clinical cases, showing, in parallel, children diagnosed with Type 1 Diabetes, who, facing the same stress factor -infection-, show a different response of their immune system. A conscientious maintenance of the disease, regular check-ups and a good knowledge of the risk factors are the key to avoid the occurrence of diabetic ketoacidosis.